2015
DOI: 10.1016/j.jaac.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Interpersonal Psychotherapy for Depressed Preadolescents: Examining Efficacy and Potential Treatment Mechanisms

Abstract: Objective To conduct a randomized controlled trial to evaluate the preliminary efficacy of family-based interpersonal psychotherapy (FB-IPT) for treating depression in preadolescents (ages 7–12) as compared to child-centered therapy (CCT), a supportive and nondirective treatment that closely approximates the standard of care for pediatric depression in community mental health. Method Preadolescents with depression (N=42) were randomly assigned FB-IPT or CCT. Pre- and posttreatment assessments included clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
(39 reference statements)
3
49
0
1
Order By: Relevance
“…IPT-A has been included in the Substance Abuse and Mental Health Services Administration’s National Registry of Evidence-Based Programs and Practices, American Psychological Association evidence-based treatments, and the Academy of Child and Adolescent Psychiatry’s practice parameters. Preliminary evidence also suggests benefits of IPT for preadolescent depression (Family-Based Interpersonal Psychotherapy for Depressed Preadolescents; Dietz, Weinberg, Brent, & Mufson, 2015) and bipolar disorder in adolescents (Interpersonal and Social Rhythm Therapy for Adolescents with Bipolar Disorder [IPSRT-A]; Hlastala, Kotler, McClellan, & McCauley, 2010). …”
mentioning
confidence: 99%
“…IPT-A has been included in the Substance Abuse and Mental Health Services Administration’s National Registry of Evidence-Based Programs and Practices, American Psychological Association evidence-based treatments, and the Academy of Child and Adolescent Psychiatry’s practice parameters. Preliminary evidence also suggests benefits of IPT for preadolescent depression (Family-Based Interpersonal Psychotherapy for Depressed Preadolescents; Dietz, Weinberg, Brent, & Mufson, 2015) and bipolar disorder in adolescents (Interpersonal and Social Rhythm Therapy for Adolescents with Bipolar Disorder [IPSRT-A]; Hlastala, Kotler, McClellan, & McCauley, 2010). …”
mentioning
confidence: 99%
“…IPT was adapted so there was much greater parental involvement—family based interpersonal therapy (FB-IPT). FB-IPT was more effective than more individually based client-centred therapy for 38 children aged  7–12 years with a depressive disorder (remission rates 66% vs 31%, p=0.04) 21. A recent moderate-sized (n=154) study showed FT to be more effective than individual therapy for children aged 7–14 years with depression 22.…”
Section: Introductionmentioning
confidence: 92%
“…While CBT is the only well-established theoretical orientation for school-aged children with depression, a recent RCT reported promising findings for Family-Based IPT with this younger age group (Dietz, Weinberg, Brent, & Mufson, 2015). CBT teaches symptom management strategies, including scheduling and engaging in pleasant activities, identifying and challenging negative thoughts, relaxing the body, and effectively solving problems.…”
Section: Introductionmentioning
confidence: 99%